Behavior of groundnut crop in fuction of the times of paralization of the irrigation - Galbiatti, João Antonio; da Silva, Maurício Nunes; Garcia, Anice; Caldeira, Daniela Soares Alves (Pesquisa Agropecuaria Brasileira, 1995)
The objective of this research was to analyse the times of paralization of the irrigation on matricial potencial of the soil water, grain production and seed quality of the groundnut (Arachis hypogaea (L.)) crop. The experiment was carried out at the Agriculture College of Jaboticabal, São Paulo, Brazil, in a "Latossol" soil. A completely randomized block design with eight replications was used. The treatments used were: A. cessation of irrigation at the beginning of flowering; B. cessation of irrigation on the fase of grain filling, and C. cessation of irrigation near to the harvesting fase. In general, a cessation of irrigation at the beginning of flowering caused the best results and reduced water and energy consumption.
Keywords: Arachis hypogaea; grain production; seed quality